Analysis of The Influence Of Perceive of Benefit, Digital Security, and Perceived Ease of Use on Intention To Purchase Using the Digital Wallet Application - Dharmawan, Donny; Rusman, Hedar; Wildan Nuryanto, Uli; Adi Cakranegara, Pandu; Munizu, Musran (SEULANGA SYSTEM PUBLISHER, 2024)
This research aims to determine how the convenience, security, benefits, and rewards of e-wallets influence consumer buying interest. This type of research is descriptive with a quantitative approach. The population in this research is all people who use e-wallets. The sampling technique employed in this study is the accidental sample method. The number of samples in this research was 100. Researchers obtained primary data from this research through interviews and questionnaire results. This research analysis uses several hypothesis tests using Partial Least Squares (PLS). Based on the research results, four dominant aspects have the potential to influence consumer purchasing interest in e-wallets. The ease of use of e-wallets, which enable transactions for various needs with just one application on a smartphone, increases consumer buying interest because it eliminates the need to carry cash, credit cards, or debit cards physically. Although the security factor is a priority, the security offered by e-wallets with security codes or pins does not yet significantly influence consumer buying interest. Financial benefits such as discounts or cashback offered by e-wallets are not the main factors influencing consumer buying interest because other factors, such as payment capacity and the amount of discounts from other non-cash payment instruments, are more significant. Rewards such as discounts and promos provided by e-wallets also do not significantly increase consumer buying interest because they are considered less critical than rewards from other non-cash payment tools.